Selection of potential biological control of Exserohilum turcicumwith epiphytic microorganisms from maize = Selección de microorganismos epifíticos de maíz como potenciales agentes debiocontrolde Exserohilum turcicum - Sartori, Melina Victoria; Nesci, Andrea Verónica; Formento, Angela Norma; Etcheverry, Miriam Graciela (Asociación Argentina de Microbiología, 2018)
The aims of this study were to select microbial isolates from phyllosphere of maizeand to examine their antagonistic activity against Exserohilum turcicum. Selection was per-formed through the ability of isolates to compete with the pathogen using an index of dominanceand to affect growth parameters of E. turcicum. Most of the epiphytic populations obtained forthe screening were bacteria. These isolates were found in the order of 6 log CFU/g of leaf freshweight. According to similar morphological characteristics and staining, 44 out of 111 isolatesobtained were selected for testing antagonistic effects. At water potential, , −1.38 MPa and−4.19 MPa, three Bacillus isolates showed dominance at a distance (5/0) and a significant reduc-tion of growth rate of the pathogen. Three Bacillus isolates only decreased the growth rate ofE. turcicum at −1.38 MPa. At −4.19 MPa the growth rate decreased with three isolates ofPantoea and three Bacillus. In this study a negative and significant correlation was observedbetween the growth rate of E. turcicum and the dominance index in the interaction of thepathogen with some bacteria. These results show that with decreasing growth rate of thepathogen the dominance index of the interaction increases. Eleven potential biocontrol agentsagainst E. turcicum were selected.